NRC proteins - a critical node for pattern and effector mediated signaling. (3rd August 2018) - Leibman-Markus, Meirav; Pizarro, Lorena; Bar, Maya; Coaker, Gitta; Avni, Adi
ABSTRACT: Plants are constantly exposed to numerous diverse microbes and pests. They lack an adaptive immune system and rely on innate immunity to perceive and ward off potential pathogens. The plant immune system enables plants to overcome invading microorganisms, and can be defined as highly successful in this regard. Nevertheless, specialized pathogens are able to overcome structural barriers, preformed defenses, innate immunity and are a persistent threat to crop and food supplies worldwide. The rapidly growing world population results in massive demands for agricultural products and reliable crop yields. Therefore, the ability to precisely manipulate plant immunity to resist diverse diseases holds significant promise for enhancing crop production.